Educação escolar e mediação: impactos das tecnologias digitais no processo de formação - Santos, Elaine Cristina Moraes [UNESP] (2015)
Considering the diffusion of digital technologies in the contemporary society, as well as its expansion in the school environment, this study has the mediation process as an analysis category, with the objective of problematizing what kind of knowledge those digital resources are able to promote. When scrutinizing the role of school practice in the society, as well as the ideological mechanisms that hide the main purpose of technological phenomena, this study contains the following hypothesis: the way in which digital technologies are included in current educational policies preclude an emancipatory educational mediation, generating evidently faced impact on the practice of the students and the human formation. This is a theoretical and bibliographic research, guided by a dialectic perspective, whose approach goes toward to the German Critical Theory of society, particularly from the reflections of Theodor Adorno, Max Horkheimer, Herbert Marcuse and Christoph Türcke